Analisa Kadar Flavonoid Fraksi Etil Asetat Ekstrak Etanol Tanaman Sawi Langit (Vernonia Cinerea L) dengan Metode Spektrofotometri Visible: Analysis Flavonoid Content Of The Ethyl Acetate Fraction Of the Sawi Langit (Vernonia Cinerea L) Ethanol Extract Using Visible Spectrophotometry Method - ELLY MULYANI; Herlina; Melani Nahdiadwi (Indonesian Journal of Pharmacy and Natural Product, 2023)
Sawi Langit (Vernonia Cinerea L) is a weed that grows wild with great potential as a medicinal plant. The purpose of this study was to determine the content of flavonoid compounds and to determine the levels of flavonoids from the ethyl acetate fraction of the ethanol extract of Sawi Langit using spectrophotometry vis. The method of this study is simplicia was extracted with 70% ethanol using the maceration method, then fractionated with n-hexane, ethyl acetate, and water (4:1:5). Thin layer chromatography test using butanol: acetic acid: water as the eluent (4:1:5). Then the concentration of the ethyl acetate fraction of the extract Sawi Langit was determined using the spectrophotometric method vis. The results of this study are identification of the ethyl acetate fraction of the ethanol extract of Sawi Langit (Vernonia cinerea L.) using layer chromatography (TLC) showed positive for containing flavonoids at a value (Rf 0.71) and quercetin standard (Rf 0.73) with a difference of 0.02. Vis spectrophotometry results in the wavelength range of 400-800 nm, showed an absorption peak at 424nm. The results showed that the flavonoid content of the Ethyl Acetate Fraction of Ethanol Extract of Mustard Greens (Vernonia Cinerea L) was 0.819%. Flavonoid compounds contained can be antioxidants and can reduce the risk of cancer, inflammation to antibacterial. ABSTRAK Sawi langit (Vernonia Cinerea L) merupakan gulma yang tumbuh liar berpotensi besar sebagai tanaman obat. Tujuan Penelitian ini adalah mengetahui kandungan senyawa flavonoid dan mengetahui kadar flavonoid dari fraksi etil asetat ekstrak etanol sawi langit menggunakan spektrofotometri vis. Metode penelitian ini adalah simplisia diekstraksi dengan pelarut etanol 70 % menggunakan metode maserasi, kemudian difraksinasi dengan n-heksan, etil asetat, dan air (4:1:5). Uji kromatografi lapis tipis (KLT) menggunakan eluen butanol: asam asetat : air (4:1:5). Kemudian dilakukan penetapan kadar fraksi etil asetat ekstrak sawi langit dengan metode spektrofotometri vis. Hasil identifikasi fraksi etil asetat ekstrak etanol sawi langit (Vernonia cinerea L.) menggunakan KLT menunjukkan positif mengandung flavonoid dengan nilai RfÂ  0,71 dan nilai Rf baku pembanding quersetin adalah 0,73, dengan selisih 0,02. Hasil spektrofotometri visible pada range panjang gelombang 400-800 nm, menunjukan puncak serapan pada 424 nm. Hasil penelitian didapatkan kadar flavonoid Fraksi Etil Asetat Ekstrak Etanol Sawi Langit (Vernonia Cinerea L) sebesar 8,2 %. Senyawa flavonoid yang terkandung dapat menjadi antioksidan dan dapat mengurangi resiko penyakit kanker, peradangan hingga antibakteri.